Environmental themes and ecosystem services in picture books about forests for sustainability education. Issue 6 (2nd November 2022) - Cho, Hye-Jung; Jo, Jang-Hwan; Choi, Naya; Choi, Jisu; Park, Wonyong
ABSTRACT: This study is based on the perspective that picture books about forests can facilitate children's knowledge and emotions about the forests, functioning as a triggering source to make children act sustainably toward forests. This study used content analysis to explore the presence and association between environmental themes and forest ecosystem services (FES) categories in 169 picture books about forests. The analysis revealed that behavioral themes (e.g. daily environmentally friendly behaviors) and the regulating services (e.g. local climate and air quality control) were less frequently presented in the picture books than other environmental themes and FES. Furthermore, several associations were identified between environmental themes and FES categories. We discuss some implications of the findings for research and practice in using picture books about forests for sustainability education.